Nanoarchitectured metal–organic framework-derived hollow carbon nanofiber filters for advanced oxidation processes. Issue 22 (24th May 2019) - Wang, Chaohai; Kim, Jeonghun; Kim, Minjun; Lim, Hyunsoo; Zhang, Ming; You, Jungmok; Yun, Jung-Ho; Bando, Yoshio; Li, Jiansheng; Yamauchi, Yusuke
Abstract : MOF-derived hollow carbon nanofiber filters (HCNFs) are designed as an efficient peroxymonosulfate catalytic reactor for the removal of organic pollutants. Abstract : Carbon materials, especially N-doped carbon materials with a one-dimensional (1D) hollow structure, have attracted great attention as one of the most efficient and eco-friendly catalysts for advanced oxidation processes (AOPs). The complex synthesis process of 1D hollow carbon however remains a major challenge in meeting the growing demand for it as a superior carbon-based catalyst. Herein, we demonstrate a facile strategy to synthesize 1D hollow carbon nanofibers (HCNFs) in a scalable manner. In this study, zeolitic imidazolate framework-8 (ZIF-8)/polyacrylonitrile (PAN) fibers were fabricated via electrospinning, and subsequent pyrolysis of the as-prepared ZIF-8/PAN composite nanofibers produced HCNFs. With excellent structural advantages and N-doped composition, HCNFs exhibited a remarkable level of catalytic degradation of tetracycline (TC) in the peroxymonosulfate (PMS) activation system. Furthermore, the HCNFs also showed good mechanical flexibility. A catalytic device was then constructed to explore the potential applications of HCNFs.